Benthic foraminiferal assemblages of the southeastern Sea of Okhotsk during the last glacial period. - Basov, Ivan A; Khusid, Tatyana A (PANGAEA, 2002)
A comparative analysis of benthic foraminiferal assemblages in the last glacial sediments obtained by gravity cores from the southern Kamchatka slope (Vulk-34-98) and from the eastern slope of the Akademii Nauk Rise in the central Sea of Okhotsk (Vulk-34-90) revealed, along with their undoubted similarity, substantial differences caused by hydrological regime in these areas during the considered period. It is shown that during the last glacial period bottom waters near the northern Kuril Islands were warmer and less aerated than those in the Akademii Nauk Rise area. As is evident from low-amplitude variations in proportions of dominant species, hydrological parameters in the bottom layer of the latter area at that time were relatively more stable than in the former area.
Benthic Foraminifera in Upper Pleistocene - Holocene bottom sediments from the southeastern Sea of Okhotsk
Keywords: Archive of Ocean Data; ARCOD; GC; Gravity corer; Sea of Okhotsk; Vulk-34-90; Vulk-34-98